Anterior Segment Findings in Vitamin A Deficiency: A Case Series - Pierangela Rubino; Paolo Mora; Nicola Ungaro; Stefano A. Gandolfi; Jelka G. Orsoni (Case Reports in Ophthalmological Medicine)
Vitamin A deficiency is a rare but vision threatening disorder in the developed world, which can lead to blindness for severe keratomalacia with cornea scarring and perforation or night blindness due to impaired dark adaptation. Conversely, the disease is quite common in developing countries, as a consequence of chronic malnutrition. The correct diagnosis and therapy with prompt vitamin A supplementation avoid blindness. We report a series of 3 local cases with different age and causes for vitamin A deficiency. The diagnostic workup, therapy, and prognosis are discussed.